Effectivity of Mobile Health as Progressive Muscle Relaxation Training Media to Premenstrual Symptoms in Adolescents - Dewi Marfuah; Dewi Srinatania; Nunung Nurhayati; Nuraini Fauziah (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
Premenstrual syndrome (PMS) is a disease characterized by mood or emotional, bodily, and behavioral symptoms of reproductive women that increase in the menstrual cycle during the luteal phase and disappear within a few days after menstruation. Approximately 50% - 80% of reproductive women suffer from PMS (approximately 3% to 8%) can cause severe mood swings, which interfere with their lifestyle and quality of life. Progressive Muscle Relaxation (PMR) is an effective way to achieve a balance between the sympathetic and the parasympathetic nervous system so reducing the impact of stress on the body. This study aim to evaluate effectivity of progressive muscle relaxation by mobile health to premenstrual syndrome in adolescent. A quantitative study using a Quasy-experimental with two Group Pre-Posttest design. Samples are 52 adolescents have experience PMS, have reguler menstrual cycle, are able to communicate well, can read and write, have cellphones/other communication tools, and willing be a respondent. Instruments using PSST for Screening of PMS and DRSP for evaluate PMS at experimental and control groups. Experimental Group given PMR by mobile health during 10 days. Bivariat analysis using Mann-Whitney test. The result of study found that grade of PMS at pretest was 15% mild, 38,5% Moderate and Severe among 48,5%. The Mann-Whitney value showed that there was a significant difference found between experimental and control group at level of p <0,001. This is reveals that there was a significant decrease to premenstrual syndrome in the experimental group after PMR. This study showed that there is a strong need for further reproductive health education. So there should be a regular service and health education programme on premenstrual syndrome and progressive muscle relaxation or exercises at all hospitals or clinic and nurses or another caregivers have an important role to do it.